Event Organization Analysis in Increasing “Westin” Brand Awareness - Sriantari, Putu Mega; Halim, Deddy Kurniawan; Lumanauw, Nelsye (Journal of Business on Hospitality and Tourism, 2022)
There are hotel developments in Bali and many new hotels, one of which is The Westin Resort & Spa Ubud Bali (TWRSUB). Organizing online events has the potential to increase brand awareness as offline events cannot be held during a pandemic. This study aims to analyze the event organization in increasing “Westin” brand awareness. The method used is quantitative by analyzing the effect (simple linear regression). Data collection is done by distributing online questionnaires to all invited guests who have attended the event at TWRSUB. Based on the results of the study, it was concluded that: a) there was a significant effect of organizing offline events at TWRSUB on visitor brand awareness, and the coefficient of determination was 0.333, which means that 33.3% of brand awareness was influenced by offline events. b) the significant effect of organizing online events at TWRSUB on visitors' brand awareness, and the coefficient of determination is 0.191, which means that 19.1% of brand awareness is influenced by online events. c) There is a difference in the effect of organizing offline events and organizing online events at The Westin Resort and SPA Ubud on the Brand awareness of visitors. Based on the research findings, the researcher suggests that the management of TWRSUB should more often hold events both offline and online in order to increase the number of visits and brand awareness to TWRSUB.